An Instance of Utilising Numismatology in Dating Biblical Texts Leviticus 27:25 as a Test Case : General Article - Hattingh, Arend (2023)
The date of the Pentateuch and its constituent parts is an ongoing debate in Old Testament studies. This article offers another way of dating a text. In Leviticus 27, which is widely regarded as an addendum to Leviticus, there is a reference to a specific currency. The study of coins, numismatology, is an expanding field, especially over the last 40 years. This article utilises numismatology to date Lev 27. The article touches on the debate of the mint in Jerusalem and the impact of the successful rebellion of Egypt on the Persian Empire. The coins found to date in Persian Yehud are discussed to identify the currency mentioned in the text of Lev 27. The article concludes that the date of Leviticus ascertained using redaction criticism is similar to the date determined for Lev 27 using numismatics.
Keywords: bibel levitikus 27,25; Leviticus 27; Pentateuch; Coins; numismatology